Cold pursuit - Neggers, Carla (Don Mills, Ont. : MIRA Books, 2008)
A prominent ambassador is killed in Washington, D.C. and hours later his stepdaughter vanished in the mountains of New England. Can Secret Service agent Jo Harper and Elijah Cameron, with his military training and mountain rescue experience, find the missing teen. Elijah believes she may be on the run.
"This large print edition, prepared especially for Doubleday Large Print Home Library, contains the complete, unabridged text of the original publisher's edition"--T.p. verso.
99563
Keywords: Ambassadors -- Crimes against; Missing persons; Secret service; Wilderness areas -- New England; Large type books; Suspense fiction